Morphology of the lateral aspects of the human cortex: an informational explanation - Moya-Salazar, Jeel; Contreras-Pulache, Hans (Frontiers in Psychology, 2025)
This article presents a novel perspective on the structure and function of the human cortex, grounded in the Sociobiological Informational Theory (SIT). SIT offers a conceptual framework that integrates biological, psychological, and social dimensions of brain activity, challenging traditional anatomical and physiological models. Under this perspective, the neocortex is interpreted as the system of consciousness, while the paleocortex is associated with unconscious processes. This approach moves beyond classical models focused solely on anatomical structures, emphasizing instead the organized, dynamic nature of brain function as embedded in broader networks. The article argues that understanding the brain in isolation (from the nervous system, personal history, culture, and socioeconomic context) is insufficient for explaining human behavior and cognition. Consequently, SIT advocates for a rethinking of neurohistology, neuroanatomy, and neurophysiology, shifting from a static, disembodied view of the brain to a more integrated and coherent understanding of the living person—a new anatomy. This alternative interpretation of the human cortex, and of the body more broadly, opens avenues for interdisciplinary dialogue, encouraging exploration of the deep connections between consciousness, personality, and society.